2012
DOI: 10.1016/j.neuropharm.2011.01.044
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia and tobacco smoking comorbidity: nAChR agonists in the treatment of schizophrenia-associated cognitive deficits

Abstract: Tobacco smoking is a preventable cause of morbidity and mortality throughout the world. Very high rates of tobacco smoking are seen in patients with schizophrenia. Importantly, smokers with schizophrenia generally have higher nicotine dependence scores, experience more severe withdrawal symptoms upon smoking cessation, have lower cessation rates than healthy individuals, and suffer from significant smoking-related morbidity and premature mortality compared with the general population. Interestingly, significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
78
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(82 citation statements)
references
References 156 publications
4
78
0
Order By: Relevance
“…Studies demonstrate nicotinic receptor antagonists worsen these symptoms (Tandon, 1999), as does smoking abstinence (George et al, 2002), with symptom improvement upon resumption of smoking behavior (Sacco et al, 2005). Furthermore, preclinical evidence points to the potential utility of nicotinic agonists for alleviating the cognitive deficits associated with schizophrenia, further highlighting how nicotine may ameliorate some symptoms (D'Souza & Markou, 2012). Smoking may also decrease medication-induced side-effects, specifically, extrapyramidal symptoms (Goff, Henderson, & Amico, 1992) that may contribute to a lack of adherence (Tandon, 2011).…”
Section: How Might Comorbid Psychiatric Disorders Such As Schizophrementioning
confidence: 99%
“…Studies demonstrate nicotinic receptor antagonists worsen these symptoms (Tandon, 1999), as does smoking abstinence (George et al, 2002), with symptom improvement upon resumption of smoking behavior (Sacco et al, 2005). Furthermore, preclinical evidence points to the potential utility of nicotinic agonists for alleviating the cognitive deficits associated with schizophrenia, further highlighting how nicotine may ameliorate some symptoms (D'Souza & Markou, 2012). Smoking may also decrease medication-induced side-effects, specifically, extrapyramidal symptoms (Goff, Henderson, & Amico, 1992) that may contribute to a lack of adherence (Tandon, 2011).…”
Section: How Might Comorbid Psychiatric Disorders Such As Schizophrementioning
confidence: 99%
“…Specifically, elevated average smoking rates 460% have been reported in patients suffering from schizophrenia (Dome et al, 2010). Different theories implicate nicotine intake via smoking as a compensatory strategy used by schizophrenia patients to ameliorate their symptoms (D'Souza and Markou, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, postmortem studies and pharmacological challenges have reported further evidence of decreased expression levels of a 7 -nAChR in patients with schizophrenia (D'Souza and Markou, 2012;Martin-Ruiz et al, 2003). At the behavioral level, the stimulation of a 7 -nAChR through nicotine intake has been demonstrated to improve working memory and selective attention deficits, and to enhance thalamocortical functional connectivity in schizophrenia patients (Jacobsen et al, 2004;Sacco et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations